Glioblastoma radiotherapy using Intensity modulated Radiotherapy (IMRT) or proton Radiotherapy-GRIPS Trial (Glioblastoma Radiotherapy via IMRT or Proton BeamS): a study protocol for a multicenter, prospective, open-label, randomized, two-arm, phase III study - König, Laila; Jäkel, Cornelia; Knebel Doeberitz, Nikolaus von; Kieser, Meinhard; Eberle, Fabian B.; Münter, Marc; Debus, Jürgen; Herfarth, Klaus (Radiation oncology, 2021)
Radiation therapy is an integral part of the multimodal primary therapy of glioblastomas. As the overall prognosis in this tumor entity remains unfavorable, current research is focused on additional drug therapies, which are often accompanied by increases in toxicity. By using proton beams instead of photon beams, it is possible to protect large parts of the brain which are not affected by the tumor more effectively. An initial retrospective matched-pair analysis showed that this theoretical physical benefit is also clinically associated with a reduction in toxicity during therapy and in the first few months thereafter.